2012 15th International Power Electronics and Motion Control Conference (EPE/PEMC) 2012
DOI: 10.1109/epepemc.2012.6397313
|View full text |Cite
|
Sign up to set email alerts
|

Power quality improvement of small hydro station

Abstract: Paper presents generation system dedicated to small hydro power station. The conventional generation system uses cage induction generator which demand of reactive power is very high and then its power quality in transients and steady state is very poor. To improve the quality of power, a three level NPC power electronic parallel compensator is applied. The generation system reactive current and power is controlled using voltage oriented method. The rotating x-y frame responds space vector of the grid voltage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For these conditions component u Mx equals U M and u My equals zero [10], [11]. The output signal of the DC-bus voltage regulator Ru DC establishes the reference signal i * P x , and i * P y is referenced from stator voltage controller Ru M or reactive power controller Rq G depending on the operation mode.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these conditions component u Mx equals U M and u My equals zero [10], [11]. The output signal of the DC-bus voltage regulator Ru DC establishes the reference signal i * P x , and i * P y is referenced from stator voltage controller Ru M or reactive power controller Rq G depending on the operation mode.…”
Section: System Descriptionmentioning
confidence: 99%
“…However, in both systems the induction generator demand on the reactive power is covered by the grid, so the capacitor bank is used to partially compensate for reactive power demand [8], [9]. As the reactive power of the induction machine depends on its active power, the parallel-connected electronic converter might precisely satisfy variable profile reactive power demand [9]- [11]. Connection of an excited induction generator to the grid without an inrush current, i.e., with synchronization, is possible, but the source of mechanical power should be equipped with a precise speed controller [12].…”
Section: Introductionmentioning
confidence: 99%
“…A reactive power compensation is usually provided by capacitor bank, but that solution does not allow to precise reduce the reactive power delivered from the grid (Sharaf et al, 2010). A capacitor bank may be replaced by the STATCOM, which delivers a reactive power precisely as much as the induction generator needs (Aparna et al, 2017;Swagat et al, 2018;Wi sniewski et al, 2012;Wi sniewski and Koczara, 2013), as it is shown in Figure 1. The parallel electronic compensator is a compromise between simplicity and robustness of capacitor banks compensator and cost and controllability of back-to-back converter interface (Meier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This increases the losses and needs the de-rating of the machine. These power quality issues can be mitigated to increase the system efficiency as discussed in [16,17]. Authors have worked on a hybrid system control and operation.…”
Section: Introductionmentioning
confidence: 99%